Kajian Pemetaan Desa Rantau Mapesai sebagai Langkah Strategis Pengelolaan Wilayah di Indragiri Hulu - Trisnawati, Lisa; Guntur, Sri; Dianti, Rina; Erny, Erny; Hendri, Hendri (Yayasan Pendidikan Intan Cendekia, 2023)
Rantau Mapesai Village is located in Rengat District, Indragiri Hulu Regency, Riau Province. The village has an area of 5000 ha, consisting of two areas, namely Hamlet I Beringin and Hamlet II Jaya which are divided into 4 Rukun Warga and 8 Rukun Tetangga. Rantau Mapesai Village requires a village map as a source of information that can be used as a support in implementing government activities in the village. This community service activity aims to produce a map of Rantau Mapesai Village, so that with this map it can be seen the position of the village in the surrounding area, identify village potentials, can be used as a basis for making village development policies and so on. The method used in this activity is to conduct initial observations/surveys and identify problems, obtain a statement letter willing to cooperate with partners, the stages of preparation and retrieval of mitigation data and other supporting data, processing data, making map layouts, consulting the results of the layout to the village head and his apparatus. village and submission of files or printouts. The final result of this community service activity is an image map showing the layout of the geospatial information map that can be found in Rantau Mapesai Village. This Mapesai Rantau Village map can be used as a supporting material in the implementation of government activities in the village